Nutrition Education on The Importance of Breakfast Using Peerleader With Numbered Head Together (NHT) Method Through Comics and Video Media For Students Thamavitya Mulniti School Thailand - Fauziah Nasution; Fitriani Pramita Gurning; Aslam Bensulong (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Good nutrition during adolescence can be done by getting used to implementing healthy intake by fulfilling the concept of balanced nutrition. Prevalence of Malnutrition: Thailand has recorded progress in reducing the level of malnutrition, especially PEM (Protein Energy Deficiency), but there are still some teenagers who are vulnerable experiencing malnutrition, especially in poor and rural areas, apart from that, the problem of adolescent obesity in Thailand is also a nutritional problem in the world. The aim of the service is to provide health education to teenage school children about the importance of breakfast using peer leaders using the numbered heads together (nht) method through comic media. This service method is Asset Based Community Development (ABCD) using peer leaders with the numbered head together (nht) method through comic and video media towards healthy breakfast habits in junior high school students or teenagers at Thamavitya Mulniti School. The results of the service showed that the use of Peer Leaders using the Numbered Head Together (NTH) method using comic and video media was very effective in increasing respondents' knowledge by 79.6%. The suggestion in this service is that schools can make a policy in bringing breakfast supplies to school, which can indirectly monitor school children's breakfast according to balanced nutrition Keyword: Importance of Breakfast, Peer Leader, Numbered Head Together (NHT)